1987
DOI: 10.3109/00498258709043933
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that epichlorohydrin is not a toxic metabolite of 1,2-dibromo-3-chloropropane

Abstract: The major urinary metabolite of 14C-epichlorohydrin, after oral administration to rats, was identified previously (Gingell et al. 1985) to be N-acetyl-S-(3-chloro-2-hydroxypropyl)-L-cysteine (ACPC) at 36% of the administered dose. In a similar study reported here, 1,2-dibromo-3-chloropropane (DBCP) was metabolized to at least 20 radioactive urinary metabolites. ACPC was only a minor metabolite (4%) of DBCP. Epichlorohydrin was metabolized in vitro by rat liver microsomes to alpha-chlorohydrin, but DBCP was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The major urinary NAC conjugate of DBCP was identified by mass spectrometry as 7V-acetyl-S-(3-chloro-2hydroxypropyl)cysteine (III) and is in agreement with a previous report (28). It has been proposed that this metabolite may be formed by either direct GSH conjugation of DBCP or conjugation of l-bromo-3-chloroacetone (27), a cytochrome P450 metabolite of DBCP (14).…”
Section: Discussionsupporting
confidence: 90%
“…The major urinary NAC conjugate of DBCP was identified by mass spectrometry as 7V-acetyl-S-(3-chloro-2hydroxypropyl)cysteine (III) and is in agreement with a previous report (28). It has been proposed that this metabolite may be formed by either direct GSH conjugation of DBCP or conjugation of l-bromo-3-chloroacetone (27), a cytochrome P450 metabolite of DBCP (14).…”
Section: Discussionsupporting
confidence: 90%
“…In principle, conjugate addition of GSH to 2-bromoacrolein hydroxypropyl)glutathione, has been proposed to originate either from l-bromo-3-chloroacetone (Dohn et al, 1988) or via the intermediacy of an episulfonium ion (Dohn et al, 1988;Gingell et al, 1987). The former pathway involves oxidation at C2 and involves metabolic elimination of a hydrogen (or deuterium) atom at the C2 positions of DBCP.…”
Section: Resultsmentioning
confidence: 99%
“…Initial studies on the mechanism of DBCP bioactivation have proposed metabolic activation via the intermediacy of epichlorohydrin or epibromohydrin (11). However, a role for these electrophilic species in the metabolic activation of DBCP has since been refuted (12). In an alternative proposal it has been suggested that 2-bromoacrolein or l-bromo-3-chloroacetone may be involved in the testicular toxicity or nephrotoxicity of DBCP (13).…”
Section: Introductionmentioning
confidence: 99%